(untitled) (MINDEN Journal of History and Archaeology, 2025)
This research examines the Sabah Museum’s pivotal role in preserving and promoting the cultural and historical heritage of Sabah through its artifact collection, archaeological research, and community collaboration. The museum's collection also reflects the rich diversity of local cultures, with numerous artifacts donated by the local community, including indigenous groups such as the Murut and KadazanDusun. The research highlights the museum’s crucial role in both preserving tangible artifacts and safeguarding intangible cultural knowledge. Through its efforts in excavation, conservation, and public education, the Sabah Museum serves as a leading institution in the region’s heritage preservation, fostering a deeper understanding of Sabah’s history and cultural significance. The museum’s ongoing initiatives ensure that Sabah’s diverse heritage continues to be valued and shared with future generations. Keywords: Archaeological excavation, artifact conservation, cultural heritage management, indigenous knowledge, Sabah Museum